The Social World of a Child and Language Learning A Socio-constructivist Perspective - Sharma, Sujata (JOURNAL OF INDIAN EDUCATION, 2016)
English language learning has undergone a major change in the way knowledge is transacted and acquired, with social constructivism being a crucial backdrop, wherein learners negotiate and arrive at shared meaning through peer and group activities. This paper explores the journey of social constructivism as a major impact on language learning. How meaningful negotiation by learners in groups through teacher intervention acts as a support for enhanced acquisition of language is highlighted in the paper with illustrations.